Tradução para o português e validação do questionário para avaliar a capacidade funcional "Stanford Health Assessment Questionaire" - Ferraz, Marcos Bosi [UNIFESP] (1990)
Functional ability evaluation constitutes an important outcome measurement in any proposed trial involving patients with rheumatoid arthritis (RA). A crosscultural study was performed directed at the translation into Portuguese of the Health Assessment Questionnaire (HAQ) and the evaluation of its measurement properties. Five questions were modified in the Portuguese version of the HAQ to suit Brazilian conditions. The test-retest correlation coefficient was 0.905 (p<0.001) and the inter -observer correlation coefficient was 0.830 (p<0.001). The instrument kept its face, content and longitudinal construct validity. The responsiveness of the Portuguese version of the HAQ is somewhat similar to the one presented by the number of tender and swollen joints, measurement considered as the most preferable endpoint in RA trials. These data allow the use of the Portuguese version of the HAQ as a valuable evaluative instrument.